Sosialisasi Marketing Communication dalam Meningkatkan Sadar Wisata di Desa Tanjung Luar Lombok Timur - Masbullah Masbullah; Salmi Yuniar Bahri (Universitas Pahlawan Tuanku Tambusai, 2022)
This Community Service activity was carried out in Tanjung Luar Village, East Lombok in the form of marketing communication socialization activities in increasing tourism awareness in Tanjung Luar Village. The goal is to understand public relations, personal selling, sales promotion and advertising, and improve through the application of information systems and technology and create relevant policy models. This PKM uses qualitative and field survey methods to reveal and find out the real social reality of the community. Informants who are used as partners and the main source of information are from the Tanjung Luar village government. The focus of socialization of marketing communications is to advance and promote this tourist area through individual expertise and online and in-person promotions. The results achieved in this activity are the results of effective communication for the surrounding community through online communication, implementing the potential of the Tourism Village through public relations activities, personal selling, sales promotion and advertising and packaged through system advancements and information manually and directly.